Investment Behavior and the Small Firm Effect - Robert J. Sweeney; Robert F. Scherer; Janet Goulet; Waldemar M. Goulet (Journal of Entrepreneurial and Small Business Finance, 1996)
Our purpose in this review is to develop one explanation of market behavior which is consistent with the many empirical findings that appear to be inconsistent with the market efficiency hypothesis. To date, researchers have attempted to reconcile their empirical results with market efficiency based on either measurement error or structural inefficiencies. We propose a different approach to market efficiency. We posit that the empirical findings previous researchers report are by their nature ex post, and are a direct result of a market which is best described as efficient. We develop a model and provide a simulation to support this explanation.
Keywords: G12; L25; G14; 650; Small Firm Effect; Asset Pricing